Alterations in Plasma Amino Acid Levels in Chronic Pancreatitis - Girish, Banavara Narasimhamurthy; Rajesh, Gopalakrishna; Vaidyanathan, Kannan; Balakrishnan, Vallath (JOP. Journal of the Pancreas, 2011)
Context Dietary proteins and amino acids can modulate pancreatic function. Objective Our aim was to estimate the levels of plasma amino acids in chronic pancreatitis patients and study their relationship with disease characteristics as well as exocrine and endocrine insufficiency. Patients One hundred and seventy-five consecutive adult patients with chronic pancreatitis: 84 patients with alcoholic chronic pancreatitis and 91 patients with tropical chronic pancreatitis. One hundred and thirteen healthy controls were also studied. Design Prospective study. Main output measures Disease characteristics and imaging features were recorded. Plasma-free amino acid levels were estimated using reverse-phase high-performance liquid chromatography. Polyclonal antibody ELISA was used to assess pancreatic fecal elastase-1. Results The majority of the plasma free amino acid levels decreased in chronic pancreatitis patients whereas glutamate, glycine, proline and lysine were elevated as compared to the controls. Multivariate logistic regression analysis revealed that the decrease in branched chain amino acid concentration was significantly associated with the presence of diabetes and low fecal elastase-1. In addition, a significant positive correlation was observed between branched chain amino acids and pancreatic elastase-1 (rs=0.724, P<0.001). Conclusion Reductions of plasma amino acid levels are seen in chronic pancreatitis, particularly sulphur containing amino acids and branched chain amino acids. Selective amino acid deficiencies seem to correlate with exocrine and endocrine insufficiency. Image: Amrita Institute of Medical Sciences. Cochin, Kerala, India.